2022
DOI: 10.1530/ec-21-0504
|View full text |Cite
|
Sign up to set email alerts
|

Non-thyroidal illness syndrome predicts outcome in adult critically ill patients: a systematic review and meta-analysis

Abstract: We performed a systematic review and meta-analysis to comprehensively determine the prevalence and the prognostic role of nonthyroidal illness syndrome (NTIS) in critically ill patients. We included studies that assessed thyroid function by measuring the serum thyroid hormone level and in-hospital mortality in adult septic patients. Reviews, case reports, editorials, letters, animal studies, duplicate studies, and studies with irrelevant populations and inappropriate controls were excluded. A total of 6869 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…[16] The concept that NTIS represents an independent predictor of poorer outcome in critically ill patients is increasingly being consensus. [17] Coronavirus disease 2019 (COVID-19), a new global pandemic with sudden outbreak, rapid spread, and alarming mortality, has drawn lots of attention worldwide. It was reported that approximately 14.47% (34/235) of COVID-19 patients were associated with NTIS to some degree and NITI was also associated with the severity of prognosis of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…[16] The concept that NTIS represents an independent predictor of poorer outcome in critically ill patients is increasingly being consensus. [17] Coronavirus disease 2019 (COVID-19), a new global pandemic with sudden outbreak, rapid spread, and alarming mortality, has drawn lots of attention worldwide. It was reported that approximately 14.47% (34/235) of COVID-19 patients were associated with NTIS to some degree and NITI was also associated with the severity of prognosis of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…During acute pathologic conditions, such as sepsis, myocardial infarction, stoke or after complex surgical procedures necessitating prolonged intensive care treatment, a substantial portion of individuals (according to a recent large meta-analysis, about 58% of patients [ 43 ]) develop a condition defined as nonthyroidal illness syndrome (NTIS), also known as the euthyroid sick syndrome or the sick euthyroid syndrome. NTIS is characterized by decreased serum thyroid hormone levels without a corresponding increase in thyroid-stimulating hormone secretion.…”
Section: Discussionmentioning
confidence: 99%
“…NTIS has been significantly associated with high complication rates and poor prognoses across various diagnostic groups. A recent meta-analysis confirmed NTIS as an independent predictor of mortality in critically ill patients [ 43 ]. Reduced concentrations of thyroid hormones may be implicated in altered cardiac inotropism and chronotropism, altered vasoactive properties, diminished cognitive status with lethargy, inability to control bacterial infections, respiratory muscle weakness, reduced synthesis of pulmonary surfactant, and decrease of lung compliance resulting in the impairment of lung function [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation